2020
DOI: 10.3802/jgo.2020.31.e13
|View full text |Cite
|
Sign up to set email alerts
|

Pathologic discrepancies between colposcopy-directed biopsy and loop electrosurgical excision procedure of the uterine cervix in women with cytologic high-grade squamous intraepithelial lesions

Abstract: Objective: To investigate pathologic discrepancies between colposcopy-directed biopsy (CDB) of the cervix and loop electrosurgical excision procedure (LEEP) in women with cytologic high-grade squamous intraepithelial lesions (HSILs). Methods: We retrospectively identified 297 patients who underwent both CDB and LEEP for HSILs in cervical cytology between 2015 and 2018, and compared their pathologic results. Considering the LEEP to be the gold standard, we evaluated the diagnostic performance of CDB for identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 30 publications
3
19
0
5
Order By: Relevance
“…In the same study, it was emphasized that in various studies that it is difficult to differentiate LSIL and HSIL with colposcopic cervical biopsy, and therefore pathologists use immune-histochemical staining for cases in-between [25,26]. In addition, like our results, all these studies indicate that the consistency between smear and histologic results increases for more invasive lesions of the cervix [19,[23][24][25][26][27].…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…In the same study, it was emphasized that in various studies that it is difficult to differentiate LSIL and HSIL with colposcopic cervical biopsy, and therefore pathologists use immune-histochemical staining for cases in-between [25,26]. In addition, like our results, all these studies indicate that the consistency between smear and histologic results increases for more invasive lesions of the cervix [19,[23][24][25][26][27].…”
Section: Discussionsupporting
confidence: 81%
“…A prospective study shows that colposcopic biopsy results report lower rates of HSIL than LEEP [24]. In the study of Kim and et al [24], in terms of HPV detection, 67.7% concordance was found between colposcopic biopsy and LEEP results and 26.6% of the colposcopic biopsy results was under-diagnosis. In the same study, it was emphasized that in various studies that it is difficult to differentiate LSIL and HSIL with colposcopic cervical biopsy, and therefore pathologists use immune-histochemical staining for cases in-between [25,26].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The diagnostic discrepancy between CDB&ECC and conization has been reported in previous studies, reporting an underdiagnosis rate ranging from 6.4% to 23.1%. 7,[12][13][14][15][16][17][18][19] The diagnostic agreement between CDB&ECC and conization was 43-85.8% according to those studies, and our study reported a relatively high concordance rate, 72.4%. As the last step of the "threestep" screening procedure, CDB&ECC is the most convincing procedure before diagnostic conization.…”
Section: Discussionsupporting
confidence: 56%
“…Some underdiagnosed lesions were further diagnosed as invasive cancer by conization, which were occult and easy to miss. 6,7 Diagnostic cervical conization requires omnidirectional cervical sampling, which can greatly improve the early diagnostic rate of early-stage invasive cervical cancer and identify occult cervical cancer.…”
Section: Introductionmentioning
confidence: 99%